Conceptualizing food systems for global environmental change research - Ericksen, Polly J. (Elsevier, 2008)
This paper outlines a framework for studying the multiple interactions of broadly defined food systems with global environmental change and evaluating the major societal outcomes affected by these interactions: food security, ecosystem services and social welfare. In building the framework the paper explores and synthesizes disparate literature on food systems food security and global environmental change, bridging social science and natural science perspectives. This collected evidence justifies a representation of food systems, which can be used to identify key processes and determinants of food security in a given place or time, particularly the impacts of environmental change. It also enables analysis of the feedbacks from food system outcomes to drivers of environmental and social change, as well as tradeoffs among the food system outcomes themselves. In food systems these tradeoffs are often between different scales or levels of decision-making or management, so solutions to manage them must be context-specific. With sufficient empirical evidence, the framework could be used to build a database of typologies of food system interactions useful for different management or analytical purposes.